2009
DOI: 10.3354/meps07713
|View full text |Cite
|
Sign up to set email alerts
|

Comparative foraging ecology of a tropical seabird community of the Seychelles, western Indian Ocean

Abstract: We studied the foraging ecology of a tropical seabird community in 2 islands of the Seychelles from 2005 to 2007. Chick dietary samples were used to compare feeding habits among species and assess inter-annual and seasonal variations in diet. Fish prey dominated the diet of the community (68 to 100% of prey consumed), although cephalopods were present in 61.3, 40.0, 27.1 and 32.9% of the food samples from white-tailed tropicbirds, sooty terns, brown noddies and wedgetailed shearwaters, respectively. We found h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 29 publications
2
76
0
Order By: Relevance
“…Mean prey lengths were almost the same; 70.0 mm and 70.7 mm for Common Noddy and Sooty Tern, respectively. The Morisita-Horn overlap index of dietary composition indicated a significant overlap of 0.851 between the two species (Catry et al, 2009). Another study on regurgitated prey items of Sooty Tern chicks from four different islands in the Mozambique Channel and Seychelles by the same team found that they were fed significantly different proportions of types of food, reflecting changes in prey availability and seasonality of breeding (Jaquemet et al, 2008).…”
Section: Species and Sampling Sitementioning
confidence: 98%
See 4 more Smart Citations
“…Mean prey lengths were almost the same; 70.0 mm and 70.7 mm for Common Noddy and Sooty Tern, respectively. The Morisita-Horn overlap index of dietary composition indicated a significant overlap of 0.851 between the two species (Catry et al, 2009). Another study on regurgitated prey items of Sooty Tern chicks from four different islands in the Mozambique Channel and Seychelles by the same team found that they were fed significantly different proportions of types of food, reflecting changes in prey availability and seasonality of breeding (Jaquemet et al, 2008).…”
Section: Species and Sampling Sitementioning
confidence: 98%
“…The Sooty Tern is also the most abundant tropical marine species, with 6 million pairs estimated to breed in the southwest Indian Ocean (Feare et al, 2007;Jaquemet et al, 2008). Its chicks regurgitated very much the same prey items as the Common Noddy; 82% of the fish items were made up of Mullidae (35%), Carangidae (10%), Engraulidae (9%), Exocoetidae (19%), and fish larvae (1%) (Catry et al, 2009). Cephalopods contributed 18% of prey items.…”
Section: Species and Sampling Sitementioning
confidence: 99%
See 3 more Smart Citations